Linguistics Politeness in Reinforcing Character During Learning Activities - Nashruddin Nashruddin; Liqaa Habeb Al-Obaydi (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Character education is an effort that is designed and carried out systematically to help students understand the values ​​of human behavior. The current research aimed at: (1) investigating the formation of politeness in the language of learning interactions between teachers and students, (2) analyzing the application of politeness principles as a part in the implementation of character education. The current research applied the descriptive qualitative method. The subjects of this study were 21 students of XI-class and an EFL teacher at SMK Dirgantara Makassar in the learning activity. The data was collected by using the recording technique and note taking. After the data was collected, the researchers analyzed the data by applying the conversation analysis with three concepts, namely data reduction, data display, and conclusion drawing or verifications. The result of data analysis found that convey messages properly required using politeness ways. Secondly, in carrying the learning process, teachers should be based on the rules and procedures for polite delivery content, language, and manners. Finally, the conclusions remarks stated that the application of politeness is one of the main factors to achieve character education. This is evidenced by the students’ habit in daily communicating politely after the linguistics politeness was applied in learning activities.